The power of participation? Power relations and processes in employee-owned companies - Thomas Steger; Ronald Hartz (Zeitschrift für Personalforschung (ZfP), 2008)
Introducing employee participation in a company can be expected to change the power relations and the power processes within the organization. This is particularly true when the majority ownership of a company moves into the hand of its employees. Drawing on three case studies of East German companies this paper describes how the introduction of employee ownership interrelates with power relations and processes in the company. Moreover, some overarching patterns were derived from the analysis finally resulting in seven propositions about how employee ownership and power are linked to each other. – – Die Einführung von Mitarbeiterkapitalbeteiligung in einem Unternehmen lässt in der Regel auch die Machtverhältnisse und Machtprozesse innerhalb der Organisation nicht unberührt. Das gilt insbesondere in jenen Fällen, wo die Mehrheit der Unternehmensanteile in die Hände der Mitarbeiter übergeht. Auf der Grundlage von drei Fallstudien in ostdeutschen Unternehmen wird beschrieben, in welchem Interaktionsverhältnis die Einführung von Mitarbeiterkapitalbeteiligung und die Machtverhältnisse und -strukturen in den betroffenen Unternehmen stehen. Darüber hinaus werden firmenübergreifende Muster herausgearbeitet, die in sieben Thesen über das Verhältnis zwischen Mitarbeiterkapitalbeteiligung und Macht münden.
Keywords: 330; employee ownership; employee-owned company; power; small and medium-sized enterprises; company crisis; east Germany; Mitarbeiterkapitalbeteiligung; KMU; Krisenmanagement; Macht; Neue Bundesländer